2013
DOI: 10.5005/jp-journals-10024-1466
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Temporomandibular Joint Dysfunction and Its Signs among the Partially Edentulous Patients in a Village of North Gujarat

Abstract: There is disagreement about the association between missing teeth and the presence of temporomandibular disorder (TMD).Aim: To investigate whether, the span of edentulousness, gender, number of quadrants involved, pathological migration and the type of kennedy's classification are related to the temporomandibular joint (TMJ) dysfunction signs. Materials and methods:Clinical examination of 250 patients (males 99 and females 151) was done among the age group of 35 to 45 years. The patients were partially edentul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 12 publications
1
25
1
7
Order By: Relevance
“…A higher prevalence was observed in the group of 60-69 years, agreeing with the results of Yekkalam et al 2 , Swiri et al 10 , Guarda-Nardini et al 15 , Peñón et al 16 , and Shet et al 21 . Each organism has the capacity to adapt itself to events that affect orthopedic stability.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…A higher prevalence was observed in the group of 60-69 years, agreeing with the results of Yekkalam et al 2 , Swiri et al 10 , Guarda-Nardini et al 15 , Peñón et al 16 , and Shet et al 21 . Each organism has the capacity to adapt itself to events that affect orthopedic stability.…”
Section: Discussionsupporting
confidence: 89%
“…Prevalence was similar among men and women, results that differs with most other studies 1,2,5,[7][8][9][10]13,14,16,[19][20][21][22][23][24][25] , except with the findings reported by Dallanora et al 12 in the Brazilian population. TMD distribution per group according to DC/TMD varies between studies: Manfredini1 observed a higher prevalence of group I TMD, Caselín et al 9 of group II, and Guarda-Nardini 15 of group III.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations